Spousal Communication as Correlate of Intimacy and Home Management among Working Class Couples in Taraba and Adamawa States, Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
Effective spousal communication is widely regarded as a cornerstone of marital adjustment. For working-class couples managing occupational and domestic demands, communication is particularly critical for maintaining intimacy and coordinating home management. This study investigated the relationship between spousal communication and two key domains of marital adjustment, intimacy and home management, among working-class couples in Taraba and Adamawa States, Nigeria. A correlational design was employed. A sample of 398 couples was selected from six Local Government Areas using a multi-stage sampling technique. Data were collected using two validated instruments: the Spousal Communication Questionnaire (SCQ; α = 0.94) and the Marital Adjustment among Couples Questionnaire (MACQ; α = 0.85). Data analysis involved Pearson Product-Moment Correlation to examine relationships and linear regression to test hypotheses at a 0.05 significance level. Findings revealed significant positive correlations between spousal communication and both intimacy (r = .515, p < .01) and home management (r = .749, p < .01). Regression analysis confirmed that spousal communication significantly predicted intimacy (β = .515, R² = .265, p < .05) and home management (β = .749, R² = .560, p < .05). The study concludes that effective spousal communication is a vital correlate of enhanced intimacy and efficient home management. It is recommended that couples and marital counsellors prioritize the development of open, empathetic, and collaborative communication skills to foster marital adjustment.